The miscarriage of justice and epistemic injustice in eyewitness identification - Ribas Ortigosa Leite, Sara (2023)
This article intends to demonstrate that miscarriages of justice arising from eyewitness identifications failures are related to the existence of stereotypes and the phenomenon of epistemic injustice, best described by Fricker and Lackey. After all, how do these stereotypes and the epistemic injustice manifest themselves in these cases? This question will be answered based on a jurisprudential research, selecting the decisions handed down by STJ in Habeas Corpus and Criminal Review, between 03/01/2012 and 03/31/2022, which have resulted in exoneration or imprisonment relaxation due to infringement of the procedure of 226th article from CPP. The results show that the prejudices that affect black individuals, with low education and low income, with less prestigious jobs and who have already had some contact with criminal activity, are not explicitly manifested, but are decisive for the occurrence of miscarriage of justice. On the other hand, stereotypes linked to the nature of the criminal offense and the person's procedural position are not only quite explicit, but are admittedly taken into account by the court. These stereotypes constitute the main criterion for distributing credibility to the procedural subjects narratives, revealing that epistemic injustice is an important cause of miscarriage of justice.